Psychometric properties of a scale to measure the dark side of personality - Salessi, Solana Magalí (2018)
The psychometric characteristics of the Dark Triad Scale (Jones & Paulhus, 2014) in an Argentinian context are presented. Two successive studies were carried out. Three hundred sixteen people, with an average age of 34.48 years (SD = 10.57), participated in Study 1. An exploratory factor analysis indicated a three-factor structure with suitable internal consistency (Machiavellianism: α = 0.92; narcissism: α = 0.91, and psychopathy: α = 0.89). Two hundred seventy-five people, with an average age of 32 years (SD = 8.10), participated in Study 2. A confirmatory factor analysis corroborated the three-factor structure. The three factors reached satisfactory composite reliability (CR greater than 0.70) and adequate convergent-discriminant validity (AVE greater than 0.50). The invariance of the scale?s parameters was demonstrated by sex. The results indicate that the Argentinian version of the Dark Triad Scale measures the dark side of personality with appropriate validity and reliability, both in men and women.